PERAN GURU PAI DALAM MENANAMKAN NILAI-NILAI TOLERANSI BERAGAMA DI SMAN 1 TANTA - Nurhayati Nurhayati (CV. ADIBA ASIHA AMIRA, 2024)
The background of this research is the large number of students who cannot tolerate well among students of different beliefs at SMAN 1 Tanta. The purpose of this study was to find out the role of PAI teachers in instilling the values of religious tolerance, the supporting and inhibiting factors in instilling the values of religious tolerance at SMAN 1 Tanta. Researchers used field research (field research) with a qualitative descriptive approach, while data collection techniques were carried out starting from observation, interviews, documentation and data analysis, as well as data analysis techniques carried out starting from data reduction, data presentation and drawing conclusions. The results of this study are: First, PAI teachers provide motivation on the importance of tolerance to all students. Second, as a guide for Islamic religious education teachers fosters an attitude of tolerance towards all students where students become able and willing to cooperate with anyone who has a variety of backgrounds, views, and beliefs. The application of an attitude of tolerance Islamic religious education teachers in cultivating an attitude of religious tolerance as a motivator, mentor and evaluator makes students better understand religious tolerance.